e-Expense Claims System / Chong Chee Fui - Chong , Chee Fui (2001)
This Project paper is prepared as to partially fulfill the requirement of the Bachelor of Computer Science. The development of e-Expense Claims System is highlighted in this document The e-Expense Claims System is to provide computerized and useful system for faculty administrators, lecturers and students in managing information more efficiently and effectively. It has to point out that the e-Expense Claims System will not be developed specific for small and medium size commercial companies. This is to ensure that the system can easily adapt to changes and can be customized for other organization with similar needs. The main purpose of the system is to computerize the manual system. This proposed electronic system enhances the expense claims application flows. The electronic Expense Claim application system to be located in company computer network center and accessible all authorized users connected to the company office. The expense claim is then submitted electronically. The system will calculate the total value of the expense claim and check each expense against the approval rules and set each expense's approval status appropriately. The decomposition of e-Expense Claims System into module and sub modules, function and features of each module are described in this docwnent as well. The system analysis, system design, system development and testing and maintenance are also focused.